DESCRIPTION OF MEDICINAL PLANTS USED IN TREATMENT OF DIFFERENT DISEASES - Ilhomiddinova Sh.U (Scholar Express Journals, 2021)
As you know, the science of medicine in our region has long been developed. This is because of the fact that every plant that grows in our country has certain medicinal properties. Whether it grows in the mountains or in the plains or in the desert, it has healing properties. In addition, the leading scientists in the field of medicine became famous all over the world. In this article, we will focus on some of these medicinal plants that have been used in diseases related to blood pressure, based on the information provided in the literature
Keywords: Medical science; medicinal plants; mountainous area; plain